HUBUNGAN MINAT BELAJAR MATA DIKLAT MUATAN LOKAL DENGAN HASIL BELAJAR KEWIRAUSAHAAN SISWA KELAS X PROGRAM KEAHLIAN TEKNIK BANGUNAN SMK NEGERI 5 PADANG - 234-242 , Nurul Suwita Pertiwi (CIVED, 2013)
This research is based on lack of student interest in local content and lower entrepreneurship school grade from viewpoint of thoroughness criteria for student of construction major class X SMKN 5 Padang. Hypothesis that is used in this research is the presence of relationship between student interests in local subject and entrepreneurship school grade for student of construction major class X SMKN 5 Padang. This research descriptive correlation with total sampling that amounted to 47 students. The subject in this research is student of construction major class X. data in this research is taken by Likert scale questionnaire, with  variable (X) is learning interest, and variable (Y) is student’s school grade. Data analysis is performed in three steps: (1) data description, (2) pre-analysis test, and (3) testing of hypothetic data.       Data is analyzed by SPSS version 16. From results of data analysis show that Pearson correlation is (r) 0.668 and signification of correlation value 0.00 which is less than 0.05. It means that there is a relationship between student learning interests in local subject and entrepreneurship school grade for student of construction major class X SMKN 5 Padang. Key words : Level learning interest, local content, entrepreneurship.